THE ROLE OF HISTORICAL, NATIONAL, AND UNIVERSAL VALUES IN THE DEVELOPMENT OF SPIRITUAL AND MORAL EDUCATION OF CHILDREN (American Journal of Interdisciplinary Research and Development, 2023)
The education of children transcends academic instruction; it encompasses the development of their spiritual and moral foundations. In this article, we explore the vital role that historical, national, and universal values play in shaping the ethical compass and spiritual growth of young minds. Recognizing and embracing these values not only enriches a child's understanding of their cultural heritage but also fosters a sense of global citizenship, contributing to a more compassionate and interconnected world.